ENT 530 Social Media Portfolio: Ellohijabs Shafshaf / Nurul Ain Shafiqa Mohammad Safari - Mohammad Safari, Nurul Ain Shafiqa (2021)
Ellohijabs Shafsaf have been joined the ELLOHIJABS since the quarter in the year 2020. Due to that Ellohijabs Shafsaf started to learnt about the basic of business such as marketing. Moreover, the marketing that were used by Ellohijabs Shafsaf is attracting the customers through teaser, puzzle and also the hard sell and soft sell skills. This is because people are likely to start entertain themselves by getting the curiosity time to time. Through the soft sell skills, Ellohijabs Shafsaf have provided some knowledge for the customers so that they can take a good care of their scarfs and able to wear it in long period. Ellohijabs Shafsaf had played the role as the dropship to the headquarter which is, I have to do the marketing and submit the order through an apps called BIZAPP. As a dropship, Ellohijabs Shafsaf didn’t have the possession through the products, and we get paid through the commission based on sales we got.